A cane-based low cost sensor to implement attention mechanisms in telecare robots - Ballesteros-Gómez, Joaquín; Urdiales-García, Amalia Cristina; Caro-Romero, Juan; Tudela, Alberto (My University, 2019)
Telepresence robots have been recently used for Comprehensive Geriatric Assessment (CGA). Since the robot can not track a person continuously, there are several strategies to decide when to check them, from cyclic checks to simple requests from users and/or caregivers. In order to adapt to the user needs and condition, it is preferable to perform CGA as soon as regularities appear. However, this requires detection of potential issues in users to offer immediate service. In this work we propose a new low cost force sensor system to detect user’s condition and attract attention of CGA robots, so they can perform a full examination on a need basis. The main advantages of this system are: i) it can be attached to any standard commercial cane; ii) its power consumption is very reduced; and iii) it provides continuous information as long as the user walks. It has been tested with several elderly volunteers in care facilities. Results have proven that the sensor readings are indeed correlated with the users’ condition.
Keywords: Robotica-Congresos; Smart cane; Rehabilitation; Gait monitoring; Microcontrollers